1999
DOI: 10.1002/(sici)1099-1166(199909)14:9<767::aid-gps7>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of two changes in service delivery on a geriatric psychiatry liaison service

Abstract: Background The impact of two changes in service delivery (alteration in the admission policy of the medical unit and the introduction of a formal liaison component to a ‘consultation only’ liaison geriatric psychiatry service) on the associated liaison geriatric psychiatry service was examined in a naturalistic study. The main null hypothesis was that the referral rate would not be influenced by either change in service delivery. Method The 30‐month study period was divided into three phases defined by the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This encouraging finding is consistent with one study (Rapp et al, 1991) but inconsistent with several earlier studies (Rapp et al, 1988b;O'Riordan et al, 1989;Koenig et al, 1988cKoenig et al, , 1992aAmes and Tuckwell, 1994;Shah and De, 1998). The study of the geriatric medicine unit may have been unusual because several liaison geriatric psychiatry research projects were conducted in the department (Shah et al, 1997(Shah et al, , 1998aShah and De, 1998;Bahareethan and Shah, 1999) and the presence of psychiatric research staff on the wards may have improved the geriatric medicine staff's ability to detect and treat depression. The evidence gathered suggests that the treatment of depression in geriatric medicine settings can be improved.…”
Section: Discusssionmentioning
confidence: 47%
“…This encouraging finding is consistent with one study (Rapp et al, 1991) but inconsistent with several earlier studies (Rapp et al, 1988b;O'Riordan et al, 1989;Koenig et al, 1988cKoenig et al, , 1992aAmes and Tuckwell, 1994;Shah and De, 1998). The study of the geriatric medicine unit may have been unusual because several liaison geriatric psychiatry research projects were conducted in the department (Shah et al, 1997(Shah et al, , 1998aShah and De, 1998;Bahareethan and Shah, 1999) and the presence of psychiatric research staff on the wards may have improved the geriatric medicine staff's ability to detect and treat depression. The evidence gathered suggests that the treatment of depression in geriatric medicine settings can be improved.…”
Section: Discusssionmentioning
confidence: 47%
“…It is then up to the GP to either treat the resident or make a referral to a mental health worker. Some authors have queried the knowledge and skills of GPs regarding both old age psychiatry and their inclination to refer to appropriate experts, while others have questioned the abilities of carers to adequately recognize symptoms of depression (Baheerathan and Shah, 1999;Snowdon, 2001;Watts et al, 2002). In a North American study, Leo et al (2002) found that very few nursing-home residents (89/4323) were referred for depression, and 65% of these referrals occurred because staff complained of behavioral problems.…”
Section: Discussionmentioning
confidence: 99%
“…So, geropsychiatric consultation is important in a general hospital. Data suggest positive effects of psychiatric referral in geriatric inpatients, which may help in making accurate diagnoses, selecting appropriate treatments, and shortening hospital stays 11–13 …”
Section: Introductionmentioning
confidence: 99%
“…Data suggest positive effects of psychiatric referral in geriatric inpatients, which may help in making accurate diagnoses, selecting appropriate treatments, and shortening hospital stays. [11][12][13] Several articles have described referrals to geriatric psychiatric consultation services in other countries. 7,11,[14][15][16][17] However, for Asia, there is a paucity of literature on this issue.…”
Section: Introductionmentioning
confidence: 99%